The 2011 Sarawak state elections: an analysis of the performance of Pakatan Rakyat (PR) component parties (PKR, PAS, DAP) - Azlan, Ariff Aizuddin; Ra'ees, Wahabuddin (IIUM Press, International Islamic University Malaysia, 2017)
This study examines the performance of Pakatan Rakyat (PR) component political par-ties (i.e. PKR, PAS and DAP) in the 2011 Sarawak state elections. The 2011 Sarawak state elections was held in April 2011 and it was a tense battle between the ruling BN and the new comer opposition Pakatan Rakyat. The book is based on the assumption that there is a linkage between PR’s campaign strategies and election manifesto and the voters’ preference. Therefore, the study investigates the linkage between campaign strategies and manifesto of Pakatan Rakyat and its performance in the 2011 Sarawak State elections. This book uses qualitative method of research for analysis of data. The data were collected from the primary sources such as formal and informal interviews, party manifestos, newspapers, documents from the Election Commission (EC) and sec-ondary sources such as books and scholarly articles. The book argues that the opposi-tion for the first time collectively campaigned as a single opposition coalition under the name of Pakatan Rakyat. The book found that even though PR did not get the two-thirds majority in the State Legislative Assembly, it succeeded to capture more seats; pointing to the fact that there is a shift of support from the incumbent BN government towards the opposition PR. However, the book also found that the main factor contributing to PR’s inability to capture more seats was its inability to reach an understanding with the local opposition political party: Sarawak National Party (SNAP).